Multifunction interferometry using the electron mobility visibility and mean free path relationship. Issue 8 (8th May 2018) - Pornsuwancharoen, N.; Youplao, P.; Amiri, I. S.; Aziz, M. S.; Tran, Q. L.; Ali, J.; Yupapin, P.; Grattan, K. T. V.
Abstract: A conventional Michelson interferometer is modified and used to form the various types of interferometers. The basic system consists of a conventional Michelson interferometer with silicon‐graphene‐gold embedded between layers on the ports. When light from the monochromatic source is input into the system via the input port (silicon waveguide), the change in optical path difference (OPD) of light traveling in the stacked layers introduces the change in the optical phase, which affects to the electron mean free path within the gold layer, induces the change in the overall electron mobility can be seen by the interferometer output visibility. Further plasmonic waves are introduced on the graphene thin film and the electron mobility occurred within the gold layer, in which the light‐electron energy conversion in terms of the electron mobility can be observed, the gold layer length is 100 nm. The measurement resolution in terms of the OPD of ∼ 50 nm is achieved. In applications, the outputs of the drop port device of the modified Michelson interferometer can be arranged by the different detectors, where the polarized light outputs, the photon outputs, the electron spin outputs can be obtained by the interference fringe visibility, mobility visibility and the spin up‐down splitting output energies. The modified Michelson interferometer theory and the detection schemes are given in details. Abstract : Plot of the mobility visibility and the change in mean free paths, μ = e τ m = e d m V F, where V F = 10 5 m s − 1 of electron in gold (Bourke and Chantler (2010 ), Physical Review Letters, 104, 206601; Gall (2015 ), Journal of Applied Physics, 119, 085101), where the mobility (input power) is fixed at 1.0 mW, the electron mass = 9.10 × 10 − 31 kilograms, the electron charge = 1.60 × 10 − 19 coulombs. The refractive index of a silicon is 1.46, GaAs = 3.66 and Au = 0.61. The fringe peak to peak is obtained at Δ t = 2.5 fs, is 0.5 × 10 − 7 m or 50 nm, where (a) the blue color is the through port output signals and the red color is the drop port output signals, (b) the black and white signals of Figure 5a. The interference fringes of the interferometer are seen at the drop port.